ANALISIS PEMBIAYAAN PROGRAM KESEHATAN IBU DAN ANAK BERSUMBER PEMERINTAH DENGAN PENDEKATAN HEALTH ACCOUNT - Sigit Riyarto, Dominirsep Dodo, LaksonoTrisnantoro, (Jurnal Kebijakan Kesehatan Indonesia, 2012)
Background: The degree of Maternal and Child Health (MCH)is still a major problem in health development in Indonesia. Onefactor that may be an obstacle in solving this problem is thelimited cost. In this context, planning and cost utilization areessential to improve so that they can produce a great impactfor the improvement of MCH. Therefore, in-depth informationabout the MCH financing situation in regions as an input todevelop efficient activities in improving MCH status is needed.Objective: To analyze health financing situation of MCH programin 2010 which sourced from government and to make policyrecommendations related to the program in Sabu Raijua District,East Nusa Tenggara Province. The situation in question isavailability, budget planning process, expenditure accuracy,and fund flow rate.Method: This was a descriptive research with a case studystrategy.Result: The total cost of MCH program was IDR 450,787,500.It was not sufficient to provide basic health services forpregnant women from early pregnancy until postpartum period.The budget proportion from the central, provincial, and districtgovernments amounted to 79.63%, 3.56%, and 16.78%,respectively. Cost allocation of the district budget was 0.80%.Planning activities of MCH program was from the district budgetthrough the development planning meeting (Musrenbang).Proposed activities in Musrenbang were dominated by physicalactivities. The cost of MCH program was spent more on directactivities and operational cost in villages and sub districts. Theimplementation of the activities was not supported by facilitiesand adequate human resources. The MCH fund disbursementfrom the central government was conducted in October-November while from the provincial and district governmentswere in July to August.Conclusion: The governmentâs commitment was still low infinancing MCH program as a priority program due to budgetdecentralization. Musrenbang activities had not demonstratedsignificant impacts on quality activities improvement and budgetallocations from the district budget. Availability of personneland health facilities greatly affected the performance of MCHprogram. Delays in funds disbursement disrupted theimplementation of activities and provided opportunities forcorruption. Therefore, the supervision function must beimproved both internal and external.Keywords: financing, maternal and child health program,health account, budget, government.